(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2022)
Opportunistic networks are one of the most increasing evolutions of MANETs. In opportunistic networks the existence of a simultaneous path is not assumed to transmit a message between a source and a destination. In opportunistic networks, path connecting to the mobile nodes never exits, mobile nodes transmit messages with each other when they get opportunity to transmit. Furthermore, nodes are not supposed to possess or acquire any information about the network topology. Routes are built dynamically, while messages are route between the source and the destination, and any possible node can opportunistically be used as next intermediate node, only if it is likely to bring the message nearer to the final destination. These features make opportunistic networks a challenging and promising field of research. In this paper we describe approach for routing in opportunistic networks, rendering old traditional routing protocols unable to deliver messages between hosts. Thus, there is a need for a new technique to route through such networks. We propose composite approach which combines concepts of Epidemic Routing and Probabilistic Routing techniques together with acknowledgement approach for better delivery. Our results show that composite routing protocol is able to provide better message delivery probability and less message delay.